PAPAN SKOR SNOOKER OTOMATIS - Utama, Hadian S.; Isa, Sani M.; Rustandy, Wendy (Universitas Tarumanagara, 2008)
Now days snooker score board still using conventional score board that is made of wood. Each time a ball got in to the pocket the players has to change score manually. With Automatic score board snooker player do not have to change the score manually. This Automatic score board can detect color of the ball witch got in to the pocket then change the score according to the color that represent some value.